1995
DOI: 10.1088/0954-3899/21/3/021
|View full text |Cite
|
Sign up to set email alerts
|

Galactic gamma rays from the inverse Compton process

Abstract: The extent to which gamma rays from inverse Compton (IC) collisions contribute to the measured gamma-ray flux in the satellite energy band (30-4000 MeV) is examined. The problems inherent in the estimate are discussed, not least the uncertainty in the scale height of cosmic-ray (CR) electrons and in the extent to which the local cosmic-ray intensity is spatially variable. Most of the paper refers to the derivation of the effective IC contribution, effective in the sense of being such as to account for the bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Chi et al calculated intensities of ~ 8 × 10 -6 photons cm -2 s -1 ster -1 and an index of ~ -1.95; they used the same photon field as Bloemen (Mathis et al 1983), but estimated the cosmic-ray electron scale height to be on the order of 5 kpc rather than 750 pc. Giller et al (1995) Using the longitude dependence correlations, we derived a spectral index of -2.2 ± 0.2, consistent with the model predictions, and lower limits of (9.7 ± 2.7) × 10 -6 photons cm -2 s -1 ster -1 in the 30-100 MeV band and (3.3 ± 0.7) × 10 -6 photons cm -2 s -1 ster -1 for E > 100 MeV toward the galactic center. Using a model containing an isotropic component, an IC component proportional to the 408 MHz synchrotron radiation, and a spatially varying emissivity with respect to H I, we found a spectral index of -1.88 ± 0.14 and average intensities of (7.9 ± 2.9) × 10 -6 photons cm -2 s -1 ster -1 in the 30-100 MeV band and (5.0 ± 0.8) × 10 -6 photons cm -2 s -1 ster -1 for E > 100 MeV.…”
Section: Discussionmentioning
confidence: 99%
“…Chi et al calculated intensities of ~ 8 × 10 -6 photons cm -2 s -1 ster -1 and an index of ~ -1.95; they used the same photon field as Bloemen (Mathis et al 1983), but estimated the cosmic-ray electron scale height to be on the order of 5 kpc rather than 750 pc. Giller et al (1995) Using the longitude dependence correlations, we derived a spectral index of -2.2 ± 0.2, consistent with the model predictions, and lower limits of (9.7 ± 2.7) × 10 -6 photons cm -2 s -1 ster -1 in the 30-100 MeV band and (3.3 ± 0.7) × 10 -6 photons cm -2 s -1 ster -1 for E > 100 MeV toward the galactic center. Using a model containing an isotropic component, an IC component proportional to the 408 MHz synchrotron radiation, and a spatially varying emissivity with respect to H I, we found a spectral index of -1.88 ± 0.14 and average intensities of (7.9 ± 2.9) × 10 -6 photons cm -2 s -1 ster -1 in the 30-100 MeV band and (5.0 ± 0.8) × 10 -6 photons cm -2 s -1 ster -1 for E > 100 MeV.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper (Giller et al 1995) examined CGRO data in some detail and concluded that for latitudes near |b| = 90 • , IC interactions are responsible for 44% of the total galactic intensity. This figure is bigger than had been estimated by others but we consider it to be valid.…”
Section: The Inverse Compton Contributionmentioning
confidence: 99%
“…In particular, detailed predictions of IC gamma-rays above 70 − 100 MeV have been made by Bloemen [15] and Chi et al [16], with estimates of the contribution by this component being up to ∼ 50% of the diffuse intensity at medium galactic latitudes (|b| = 10 • to 20 • ). An analysis of EGRET data by Giller et al [17] has suggested a contribution by IC of ∼ 30% for medium latitudes, and up to ∼ 45% toward the galactic pole, in the energy range 30 − 4000 MeV. Strong et al [12] have shown that an IC component is required to provide a good fit to the gamma-ray data from 1 MeV to 1 GeV; see also Bertsch et al [10] and Hunter et al [14].…”
Section: Introductionmentioning
confidence: 99%